Synthesis and Characterization of PES/PEG/PVA/SiO2 Nanocomposite Ultrafiltration Membrane - Silvia Widiyanti; Mita Nurhayati; Hendrawan Hendrawan; Boon Seng Ooi; Fitri Khoerunnisa (Green Engineering Society, 2023)
This study aims to synthesis and characterize PES/PEG/PVA/SiO2 composite membranes. The composite membranes were synthesized by phase inversion method with composition (% w/w) Polyethersulfone/ PES (17.25), Polyvinylalcohol/ PVA (3.58; 0.85; 1.43; 2.57; 3.57, Polyethylene glycol/ PEG (3.72), Silica/SiO2 (0.35; 0.85; 1.43; 2.57; 3.57), and Dimethyl acetamide/DMAc solvent. Composite membranes were characterized using FTIR spectroscopy, X-ray diffraction, Scanning Electron Microscopy (SEM), and water contact angle. The results showed that the interaction between PES, PVA, and SiO2 was indicated by a shift in the typical absorption spectrum of the FTIR. SEM cross-sectional photos showed that the addition of PVA and SiO2 caused significant changes in the morphology and pore structure of the PES membrane. The results of the X-ray diffractogram (X-Ray) showed a shift in the typical diffraction peaks of PES, PEG, PVA and the presence of new diffraction peaks of SiO2. The crystallinity of the membrane increased from 34.99% to 57.25% which indicated that the composite membrane was successfully synthesized. The addition of PEG/PVA/SiO2 also increased the hydrophilicity of the composite membrane. Based on these findings, it can be concluded that the PES/PEG/PVA/SiO2 composite membrane has been synthesized through the phase inversion method with the optimum composition of PES: PEG: PVA: SiO2 was 17.25%: 3.72%: 0.85%: 0.35%, respectively. The addition of PEG/PVA/SiO2 increased the hydrophilicity and modified the morphological structure of the PES membrane.